PENGARUH FAKTOR HOT (HUMAN, ORGANISASI, DAN TEKNOLOGI) TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI PRIMARY CARE DI WILAYAH KOTA SEMARANG - Asih Prasetyowati; Roro Kushartanti (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
P-Care application user satisfaction becomes a necessity to ensure reporting service performance to BPJS. The purpose of this study is to look for HOT factors (human, organization, and technology) that affect user satisfaction P-Care applications. Quantitative research type is cross sectional with Primary Care information system object. The research subject is prime care information system operator, amount 61 operators. Data analysis used multivariate regression test. Descriptive analysis of HOT factor shows that human factor is good 100%, as much as 19,7% bad organizational policy, as much as 13,1% quality of service of less good technology. In general, users are satisfied with the p-care information system, but found 9.8% dissatisfaction on the timeliness. Regression test results show that there is influence of HOT factor to user satisfaction (0,829 - 0,222 factor human + 0,131 organizational factor + 0,224 technological factor). All three HOT factors will raise satisfaction by one level. Technological factors provide the greatest influence in increasing user satisfaction